Evaluating an English Language Course for Nursing Students - Darban, Mehrnaz (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study aims to investigate into the English course for nursing in the faculty of nursing at Shahid-Beheshti University. More specifically, the study aims to identify the students’ and the instructor’s opinions about the course suggestions as regards the improvement of the English course, and the students’ need as perceived by themselves and the course instructor. This study has been designed as a case study which uses a mixed-methods approach to research. In other words, both qualitative and quantitative data were collected through the student questionnaire and instructor interview. The participants of the study were seventy nursing students in the third and fourth years of their study and one instructor in the faculty of nursing at Shahid-Beheshti University. The results of this study indicated that both the instructor and the students held positive attitudes toward the English course for nursing in terms of its aims and objectives, content and materials, teaching-learning process, and assessment. Also, the results highlighted the strengths of the English course for nursing as perceived by the participants of the study. Additionally, the results showed that the course had some weaknesses too. Based on the weaknesses, the participants suggested making some changes in the English course for nursing. For example, by extending the time of the class and adding more English courses to teach the students. They mentioned that academic writing skills and listening skills be must emphasize more in this course. Also, they agreed the technology should be integrated into the English course. Finally, the results of the study explained some implications about the English for course for nursing in the faculty of nursing at Shahid-Beheshti University in Tehran. Also, some recommendations are provided for future studies. Keywords: English for specific purposes (ESP), English for Nursing Purposes (ENP), Need analysis (NA).
ÖZ: Mevcut çalışma Shahid-Beheshti Üniversitesi hemşirelik dersi için kullanılan İngilizceyi incelemeyi hedeflemektedir. Özelde, bu çalışma İngilizce dersine ilişkin öğrenci ve öğretmen görüşlerini, İngilizce dersinin geliştirilebilmesi için önerilerini ve öğrencilerin ihtiyaçlarını hem kendilerinin hem de ders öğretmeninin bakış açısından belirlemeyi amaçlamaktadır. Bu çalışma, karma yöntem yaklaşımı kullanılarak vaka çalışması olarak tasarlanmıştır. Diğer bir deyişle, öğrenci anketleri ve öğretmen mülakatı yoluyla hem nitel hem de nicel veriler toplanmıştır. Çalışmanın katılımcıları Shahid-Beheshti Üniversitesi Hemşirelik Fakültesi’ndeki yetmiş üçüncü ve dördüncü sınıf öğrencilerinden oluşmaktadır. Çalışmanın bulguları, hem öğretmenin hem de öğrencilerin hemşireler için İngilizce dersine yönelik amaçlar/hedefler, içerik ve materyaller, öğretim-öğrenim süreci ve değerlendirme açılarından olumlu tutumları olduğunu göstermiştir. Ayrıca, bulgular çalışmanın katılımcıları açısından İngilizce dersinin güçlü yönlerini altını çizmiştir. Bulgular, dersin bazı zayıf noktaarı olduğunu da ortaya çıkarmıştır. Zayıf noktaların temelinde, katılımcılar hemşirelik için İngilizce dersinde ders saatinin uzatılması ve öğrenciler için daha fazla İngilizce dersinin eklenmesi gibi değişiklikler yapılmasını önermişlerdir. Ders içerisinde akademik yazma becerileri ve dinleme becerilerinin daha çok vurgulanması gerektiğinden de bahsetmişlerdir. Buna ek olarak, İngilizce dersinin teknolojinin de entegre edilmesi gerektiği konusunda hemfikir olmuşlardır. Son olarak, çalışmanın bulguları Shahid-Beheshti Üniversitesi Hemşirelik Fakültesi’nde sunulan Özel Amaçlı İngilizce (ÖAİ) dersi için öneriler ve gelecek çalışmalar için tavsiyeler vermektedir. Anahtar kelimeler: Özel amaçlı İngilizce (ÖAİ), Hemşirelik Amaçlı İngilizce (HAİ), İhtiyaç analizi (İA).
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2019. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language Teacher--Study and Teaching--Eastern Mediterranean University--Cyprus, North; English for specific purposes (ESP); English for Nursing Purposes (ENP); Need analysis (NA)